Total Cardiovascular and Limb Events and the Impact of Polyvascular Disease in Chronic Symptomatic Peripheral Artery Disease - Szarek Michael; Hess Connie; Patel Manesh R.; Jones W. Schuyler; Berger Jeffrey S.; Baumgartner Iris; Katona Brian; Mahaffey Kenneth W.; Norgren Lars; Blomster Juuso; Rockhold Frank W.; Hsia Judith; et al. (WILEY, 2025)
BACKGROUND:
Peripheral artery disease (PAD) is associated with heightened risk for major adverse cardiovascular and limb events, but data on the burden of risk for total (first and potentially subsequent) events, and the association with polyvascular disease, are limited. This post hoc analysis of the EUCLID (Examining Use of Ticagrelor in Peripheral Artery Disease) trial evaluated total cardiovascular and limb events among patients with symptomatic PAD, overall and by number of symptomatic vascular territories.
METHODS AND RESULTS:
In the EUCLID trial, patients with symptomatic PAD (lower extremity revascularization >30 days before randomization or ankle-brachial index <= 0.80) were randomized to treatment with ticagrelor or clopidogrel. Relative effects on total events (cardiovascular death; nonfatal myocardial infarction and ischemic stroke; acute limb ischemia, unstable angina, and transient ischemic attack requiring hospitalization; coronary, carotid, and peripheral revascularization procedures; and amputation for symptomatic PAD) were summarized by hazard ratios (HRs), whereas absolute risks were estimated by incidence rates and mean cumulative functions. Among 13 885 randomized patients, 7600 total cardiovascular and limb events occurred during a median 2.7 years of follow-up, translating to 60.0 and 62.5 events per 100 patients through 3 years for the ticagrelor and clopidogrel groups, respectively (HR, 0.96; 95% CI, 0.89-1.03; P=0.27). Among 1393 patients with disease in 3 vascular territories, event accrual rates through 3 years for the ticagrelor and clopidogrel groups were 87.3 and 97.7 events per 100 patients, respectively. Absolute risk reductions for ticagrelor relative to clopidogrel at 3 years were -0.2, 6.7, and 10.3 events per 100 patients for 1, 2, and 3 affected vascular territories, respectively (P-interaction = 0.09).
CONCLUSIONS:
Patients with symptomatic PAD have nearly double the number of total events than first events, with rates reflecting the number of affected vascular territories. These findings highlight the clinical relevance of quantifying disease burden in terms of total events and the need for long-term preventive treatments in high-risk patient populations.